1970
DOI: 10.1037/h0029359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of overtraining on reversal and extradimensional shifts in schizophrenics.

Abstract: In Experiment I, SO schizophrenic Ss were trained under one of three discrimination learning conditions: reversal (R) shift, extradimensional (ED) shift, or control. Half of the Ss in each shift condition received overtraining on the preshift discrimination. Performances of nonovertrained Ss on the R and ED shifts were very similar to performances of schizophrenic 5s tested by Nolan, Newman-Keuls analyses indicated that in Experiment I, overtraining facilitated the R shift relative to the ED shift. The result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

1972
1972
1985
1985

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…Possible effects of endocrine changes on visual memory were assessed using forms C and E of the Benton Visual Retention Test (BVRT) (Benton, 1955) with modified instructions to prevent ceiling effects, as described elsewhere (Veith et aL, 1978a). Also, a concept formation task, considered to be sensitive to visual attentional state (Mackintosh, 1965(Mackintosh, , 1969Nolan, 1970) was administered. Two comparable forms (Nolan et al, 1978), employing stimuli which varied across the dual dimensions of either weight-length or color-form, were used.…”
Section: Rt=u× +F3mentioning
confidence: 99%
“…Possible effects of endocrine changes on visual memory were assessed using forms C and E of the Benton Visual Retention Test (BVRT) (Benton, 1955) with modified instructions to prevent ceiling effects, as described elsewhere (Veith et aL, 1978a). Also, a concept formation task, considered to be sensitive to visual attentional state (Mackintosh, 1965(Mackintosh, , 1969Nolan, 1970) was administered. Two comparable forms (Nolan et al, 1978), employing stimuli which varied across the dual dimensions of either weight-length or color-form, were used.…”
Section: Rt=u× +F3mentioning
confidence: 99%
“…According to attention theory, increasingly strong attention responses should result in facilitated reversal shifts, coupled with progressively slower extradimensional shift learning (Zeaman and House, 1963, p. 194). Results consistent with this prediction from attention theory have been obtained when dimensional attention was strengthened by increasing dimensional salience (Caron, 1969) or by providing overtraining on the original discrimination (Nolan, 1970). In both instances, the procedures which increased dimensional attention facilitated reversal shifts, but made extradimensional shifts more difiicult.…”
Section: Discussionmentioning
confidence: 54%
“…Correspondingly middle class children might be expected to learn extradimensional shifts more slowly than would lower class children, since dimensional attention responses, while they clearly seem to facilitate reversal shifts, may also impede extradimensional shifts (e.g. Caron, 1969;Nolan, 1970).…”
mentioning
confidence: 99%
“…Other researchers have examined the detrimental effects of distraction and increasing problem complexity on schizophrenics' performance (Chapman & McGhie, 1962;McGhie, Chapman, & Lawson, 1965;Neale, Mclntyre, Fox, & Cromwell, 1969) to support the view that schizophrenics suffer from some attention deficit. Others have examined the attention deficit view by assessing schizophrenics' ability to shift set (Furth & Youniss, 1968;Nolan, 1968Nolan, , 1970Nolan, , 1974. Using discrimination-learning problems, Nolan (1970) reported that schizophrenics had difficulty shifting set.…”
mentioning
confidence: 99%
“…Others have examined the attention deficit view by assessing schizophrenics' ability to shift set (Furth & Youniss, 1968;Nolan, 1968Nolan, , 1970Nolan, , 1974. Using discrimination-learning problems, Nolan (1970) reported that schizophrenics had difficulty shifting set. Unfortunately, Nolan mixed and confounded reversal and extradimensional shift tasks so that it is difficult to compare his results with studies using normal subjects.…”
mentioning
confidence: 99%